The protective effects of ligustrazine on ischemic stroke: a systematic review and meta-analysis of preclinical evidence and possible mechanisms - Wang, Ziming; Wu, Zihong; Miao, Yifan; Hao, Aohan; Chen, Hao; Zhao, Shuang; Luo, Min; Guo, Shihan; Liu, Yingming; Lu, Yun (Frontiers in Pharmacology, 2024)
Ligustrazine, an alkaloid monomer extracted from the rhizome of Ligusticum striatum DC, has shown promising effectiveness in the treatment of cerebral ischemic stroke (CIS) based on numerous preclinical studies. This study aimed to assess the impact of ligustrazine on animal models of CIS and investigate its underlying mechanism of action. Through a systematic search of databases such as China National Knowledge Infrastructure (CNKI), Wanfang Database (Wanfang), VIP Database (VIP), Chinese Biomedical Literature Database (CBM), Cochrane Library, PubMed, Web of Science, and Embase, relevant studies on ligustrazine intervention in animal models of ischemic stroke were identified. Various parameters including neurological deficit score (NDS), cerebral infarction volume percentage, brain water content, inflammation-related factors, oxidative stress indicators, apoptosis indicators, and blood-brain barrier (BBB) permeability were evaluated. A total of 32 studies were analyzed, revealing that ligustrazine could notably enhance NDS, reduce cerebral infarction incidence and cerebral edema, suppress inflammation, oxidative stress, and apoptosis, as well as restore BBB permeability. These findings suggest a protective role of ligustrazine in CIS animal models, possibly through mechanisms involving inflammation reduction, oxidative stress inhibition, apoptosis suppression, and BBB repair. Nonetheless, further rigorous experiments are essential for validation.